Direct synthesis of dimethyl ether from syngas on CuOZnOMnO/SAPO-18 bifunctional catalyst. (26th October 2016) - Ateka, Ainara; Pérez-Uriarte, Paula; Sánchez-Contador, Miguel; Ereña, Javier; Aguayo, Andrés T.; Bilbao, Javier
Abstract: A high-pressure fixed-bed reactor has been used for the direct synthesis of dimethyl ether (DME) from syngas, through a single-step process using a CuOZnOMnO/SAPO-18 (CZMn/S) bifunctional catalyst. The effects of temperature (250–350 °C), space time (2.5–20 gcat h (molC ) −1 ), reaction pressure (20–40 bar) and time on stream have been studied. The results show that suitable conditions for attaining high yield and selectivity of DME are 275–300 °C, with moderate reaction pressure (30 bar). For space time values above 5 gcat h (molC ) −1, the catalyst acquires a pseudo-steady state of constant activity. The need of purifying the syngas feed (free of olefins and/or paraffins) in order to avoid the activation of the hydrocarbon pool has also been evidenced. Deactivation of CZMn/S is mainly caused by coke deposition, and three types of coke are distinguished based on its location on the catalyst: i) metal surface, ii) interface metal-MnO, and iii) acid function. Graphical abstract: Highlights: CuOZnOMnO/SAPO-18 has a good kinetic performance in the STD process. Suitable operating conditions are: 275–300 °C and 30 bar. Deactivation is mainly caused by coke deposition. Three types of coke have been identified. Hydrocarbon free feeds are required to avoid activating hydrocarbon pool mechanism.